The effect of financial crises on potential output. New empirical evidences from OECD countries - Furceri, Davide; Mourougane, Annabelle (Paris, 2009)
"The aim of this paper is to assess the impact of financial crises on potential output. For this purpose a univariate autoregressive growth equation is estimated on an unbalanced panel of OECD countries over the period 1960 to 2007. Our results suggest that the occurrence of a financial crisis negatively and permanently affects potential output. In particular, financial crises are estimated to lower potential output by around 1.5 to 2.4% on average. The magnitude of the effect increases with the severity of the crisis. The occurrence of a deep crisis is found to decrease potential output by nearly 4%, almost twice the amount observed for the average of crises. These results are robust to the use of an alternative measure of potential output, changes in the methodology and in the sample periods. "